PENGARUH STRATEGI PERMAINAN LARI KANAN-KIRI BENAR SALAH TERHADAP KETERAMPILAN DRIBBLE BOLA BASKET DI SMA - Raharjo, Fajar Puji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is how the influence of left-right game strategy is wrong against the dribble skill of basketball. The purpose of this study to find out how the influence of the game run right-left is wrong to the dribble skill of basketball game on the students of class XI in SMA Taruna Bumi Khatulistiwa Kubu Raya. This research method used experiment (one group pretest-posttes design) with quantitative descriptive. The population in this study as many as 4 classes with the number of 109 students. Sampling using sampling systematic multiples of number 5, then the number of samples is 21 students. The result of data analysis using computerized tcount of 4,035 By looking at statistics table at degrees of freedom db = (N-1) is 21-1 = 20 and 5% significance level, ttable value equal to 1.72. Based on the results of the study concluded that the game run right-left right wrong can improve learning outcomes dribble. The result of the research shows that the percentage increase is 20,67%. Furthermore the average value of the initial test is lower than the final test that is (72.86 <87.94). Thus in this study there is a significant increase. Keywords: Game, Run left right True False, Dribble